Efectos producidos por la aplicación de un biorremediador comercial sobre vibrios sp y pseudomonas sp en el suelo de estanque camaronero - Espinoza Scaldaferri, Jonathan David (2006)
The bad situation of the shrimp sector in our country, either for the fall that you/they suffered the prices, for the presence of infectious illnesses as it is the case of the WSSV or virus of the white stain and due to the absence of effective methods for the control of the activities many investigations have been developed with the desire of developing technical preventive that reduce the incidence of pathologies and that at the same time they improve the cultivation conditions. The principle of competitive exclusion of pathogens, and the decomposition of organic materials, they are two of the benefits that represents the use of microorganisms biorremediadores. This work has been developed based on the study of the used means and to the realization of analysis periodic microbiologics of the same one, which were taken in a meticulous way with the objective of gathering the required data. At the end of the investigation and with the obtained conclusions, we recommend the opening for the arrival of new investigations inside this field since the topic studied in the present is a great option to be taken into account by the productive sector.